Innovation and entrepreneurship in child nutrition: knowledge and constraints among cooking partners and caregiver mothers in the Cuna Más program - Quispe Bardales, Mariela Eraida; Alzamora De Los Godos Urcia, Luis Alex; Valladolid Marcos, Fiorella Sthefany; Calderón Saldaña, Jully Pahola; De La Rosa Condormango, Rossina Dany; Roldán Medina, Moisés; Ureta Crisóstomo, Ofelia Nora (LACCEI, 2025)
This study examines social innovation and community entrepreneurship within the National Program Cuna Más, framed as a strategy to address economic and financial crises. It focuses on the perceptions, participation, and positioning of community actors engaged in the program’s nutritional component in the districts of Jacobo Hunter (Arequipa) and Ate (Lima). Using a qualitative, descriptive, and phenomenological approach, the study explores four key dimensions: capacity building and empowerment, service delivery assessment, collaborative management, and anemia control. Data were collected through individual interviews, focus groups, and direct observation to identify structural limitations and pathways for improvement. Findings show that innovation driven by local communities can enhance child nutrition services when supported by strong organizational culture and empowered local leadership. However, critical barriers were identified, including insufficient funding, weak institutional coordination, and limited community engagement. The study concludes that fostering territorial-based social entrepreneurship strengthens the sustainability of early childhood programs like Cuna Más. It also promotes creative responses to financial constraints, supporting a social management model that is adaptive and resilient in the face of systemic challenges.